2014
DOI: 10.1097/mib.0000000000000125
|View full text |Cite
|
Sign up to set email alerts
|

High Self-efficacy Predicts Adherence to Surveillance Colonoscopy in Inflammatory Bowel Disease

Abstract: SE, as measured by our validated scales, correlates with chart-adherence to surveillance colonoscopy. Our adherence model, which includes SE, predicts adherence with 74% certainty. An 8-item validated clinical questionnaire can be administered to assess whether patients in this population may require further intervention for adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Our group recently reported that low self-efficacy to manage IBD predicted subsequent difficulties with anxiety, depressed mood, and stress one year and two years later, even when controlling for IBD symptoms in the intervening months 42 . Self-efficacy has also been found to predict adherence to recommended schedules of surveillance colonoscopy for individuals with IBD 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Our group recently reported that low self-efficacy to manage IBD predicted subsequent difficulties with anxiety, depressed mood, and stress one year and two years later, even when controlling for IBD symptoms in the intervening months 42 . Self-efficacy has also been found to predict adherence to recommended schedules of surveillance colonoscopy for individuals with IBD 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, self-efficacy was highly predictive of adherence to surveillance colonoscopy program in patients with IBD. [31] This construct was also associated with transition readiness for adult services in adolescents with IBD. [32] Perceived self-efficacy is influenced by external experiences and self-perception, and therefore it could potentially be modified according to the social cognition theory of behavioral change.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect a higher perception of risk. Friedman et al [20] found that high self-efficacy among symptomatic patients with irritable bowel disease was associated with higher adherence to surveillance colonoscopy, but perception of risk was not. This is similar to findings by Bronner et al [22] who showed that self-efficacy was associated with adherence, whereas patients who did not have screening colonoscopies tended to emphasize the reasons to abstain, such as fear and anxiety or embarrassment.…”
Section: Discussionmentioning
confidence: 99%
“…Patient health status, knowledge, attitudes and health behavior have also been examined as factors in patient adherence to CRC recommendations. In a cross-sectional study of 378 patients with Inflammatory Bowel Disease [20], high self-efficacy was strongly correlated with colonoscopy adherence (OR 1.2. adjusted for health status and patient knowledge, p < 0.001). Hay et al [21] examined the role of risk perception in promoting colorectal cancer (CRC) screening behavior in a diverse, inner city, primary care population.…”
Section: Introductionmentioning
confidence: 99%